Self-esteem, subjective well-being, and narcissistic behavior among instagram users - Fasha, Vinda Herlifa; Astuti, Rr. Dwi (Universitas Ahmad Dahlan, 2024)
The significant number of Instagram users exhibiting narcissistic behavior is a real phenomenon that underpins this study. Factors such as self-esteem and subjective well-being are known to influence narcissistic behavior. The main objective of this research is to empirically examine the relationship between self-esteem and subjective well-being with narcissistic behavior among Instagram users. Using a purposive sampling approach, 503 active Instagram users (aged between 24-45 years) comprised the study population. This research employed a quantitative methodology based on a correlational approach. Data collection instruments included the self-esteem scale, the subjective well-being scale, and the narcissistic behavior scale. Data analysis revealed an R value of 0.823, an F value of 3.021, and a p-value of 0.000 (p<0.01). The results indicate a significant relationship between self-esteem, subjective well-being, and narcissistic behavior. This study highlights the importance of enhancing self-esteem and subjective well-being among social media users to reduce excessive social comparison and envy.